2011
DOI: 10.1186/1471-2490-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of surgical repair of obstetric fistula at a regional referral hospital, Mbarara, western Uganda

Abstract: BackgroundObstetric fistula although virtually eliminated in high income countries, still remains a prevalent and debilitating condition in many parts of the developing world. It occurs in areas where access to care at childbirth is limited, or of poor quality and where few hospitals offer the necessary corrective surgery.MethodsThis was a prospective observational study where all women who attended Mbarara Regional Referral Hospital in western Uganda with obstetric fistula during the study period were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
108
7
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 18 publications
20
108
7
2
Order By: Relevance
“…7,9-12 Our results provide further evidence supporting the role of vaginal scarring and urethral involvement in predicting failure to close the fistula and residual incontinence following fistula closure. 5,7,8,10,12,13 They also support the smaller number of studies suggesting a negative prognostic role of bladder size and prior repair .6,7,12,13 So risk factors identified were involvement of the urethra, a small functional bladder capacity, increasing diameter of the fistula and the need for vaginal reconstruction. It is interesting to note that delivery method seemed protective for developing residual incontinence after fistula repair.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…7,9-12 Our results provide further evidence supporting the role of vaginal scarring and urethral involvement in predicting failure to close the fistula and residual incontinence following fistula closure. 5,7,8,10,12,13 They also support the smaller number of studies suggesting a negative prognostic role of bladder size and prior repair .6,7,12,13 So risk factors identified were involvement of the urethra, a small functional bladder capacity, increasing diameter of the fistula and the need for vaginal reconstruction. It is interesting to note that delivery method seemed protective for developing residual incontinence after fistula repair.…”
Section: Discussionsupporting
confidence: 52%
“…A number of papers have described surgical interventions, but often with much less success than that enjoyed in women without fistulas. [4][5][6][7] We found, as others have 8,9 no relationship between fistula size and successful closure after repair surgery. It is plausible that fistula size, independent of other factors, is not a predictor of repair outcome because even large defects can be surgically closed, whereas other factors such as prior repair or severe scarring (that may reduce the amount of viable tissue), or urethral involvement (that may affect sphincter mechanisms), cannot be easily addressed surgically.…”
Section: Discussionmentioning
confidence: 48%
“…First, the conventional approach until now has been to report fi stula treatment outcomes at the time of hospital discharge only, and not beyond this time. Such outcomes are generally reported to be good, with fi stula closure rates of 73-93% reported from various other African settings, [13][14][15][16][17] compared to 87% in our setting. However, repair breakdowns are known to occur in the 6-month post-operative period, 8 invalidating these hospital discharge outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…To solve this problem, the key is to decide which patient or fistula characteristics should be included in the classification system. Prior studies indicated that fistula repair outcomes were determined by certain fistula characteristics, such as fistula site, fistula size and degree of perifistula scarring [14][15][16][17] . Ayed et al [14] demonstrated that multiple fistula, fistula size and type and obstetrical etiology were associated with recurrent fistulas.…”
mentioning
confidence: 99%